Regulation of differentiation and generation of osteoclasts in rheumatoid arthritis - Niu, Qing; Gao, Jinfang; Wang, Lei; Liu, Jiaxi; Zhang, Liyun (Frontiers in Immunology, 2022)
Rheumatoid arthritis（RA）, which affects nearly 1% of the world's population, is a debilitating autoimmune disease. Bone erosion caused by periarticular osteopenia and synovial pannus formation is the most destructive pathological changes of RA, but also lead to joint deformity and loss of function, and ultimately affect the quality of life of patients. Osteoclasts(OC) are the only known bone resorption cells.,their abnormal differentiation and production play an important role in the occurrence and development of RA bone destruction and are the main culprit of rheumatoid arthritis. OC-mediated bone destruction is achieved through the regulation of a variety of cytokines and cell-to-cell interactions, including gene transcription, epigenetics and environmental factors. At present, most methods for the treatment of RA are based on the regulation of inflammation, but the inhibition of bone injury and joint deformities remains to be explored. This article will review the mechanism of abnormal differentiation of OC in RA, and summarize the current treatment of targeting cytokines in the process of OC generation and differentiation to reduce bone destruction in patients with RA, which is expected to become a valuable treatment choice to inhibit bone destruction in RA.